2007
DOI: 10.1111/j.1349-7006.2007.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel anticancer agent, benzyldihydroxyoctenone, isolated from Streptomyces sp. causes G1 cell cycle arrest and induces apoptosis of HeLa cells

Abstract: In the course of screening for anticancer agents, a novel active compound, F3-2-5, was isolated from culture broth of Streptomyces sp., KACC91015. Its structure was identified using nuclear magnetic resonance, mass spectrometry, and molecular modeling experiments, and confirmed by total synthesis. The growth of various human cancer cell lines was inhibited in a dose-dependent manner by 0.06-0.48 mM F3-2-5 over 24 h. Its IC 50 values were estimated at 37 µ µ µ µM on HeLa, 72 µ µ µ µM on A549, and 190 µ µ µ µM o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…p53 is required for efficient activation of apoptosis following irradiation and treatment with chemotherapeutic agents (90). Activation of p53-dependent apoptosis induces Bax expression, resulting in cytochrome c release from mitochondria and caspase-3 activation (91-93). Activated caspase-3 executes apoptosis by inducing cleavage of cellular substrates including PARP (93) and NF90/NF45 depletion in HeLa cells resulted in the accumulation of p53 and the 89-kDa cleavage product of PARP.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is required for efficient activation of apoptosis following irradiation and treatment with chemotherapeutic agents (90). Activation of p53-dependent apoptosis induces Bax expression, resulting in cytochrome c release from mitochondria and caspase-3 activation (91-93). Activated caspase-3 executes apoptosis by inducing cleavage of cellular substrates including PARP (93) and NF90/NF45 depletion in HeLa cells resulted in the accumulation of p53 and the 89-kDa cleavage product of PARP.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, much attention has been focused on natural products and small chemicals as potential sources of novel anticancer drugs (Park et al, 2006;Kim et al, 2007a,b;Lee et al, 2007). Thus, the identification of potential chemotherapeutic agents using mechanism-based studies holds great promise for elucidating the molecular mechanisms and devising more specific and effective treatments for cancer-related diseases.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Macherla et al (4) report that three new pyrrolosesquiterpenes isolated from a culture of Streptomyces sp., obtained from an Alaskan marine sediment, exhibited anti-tumor activity toward the colorectal adenocarcinoma HT-29 and melanoma B16-F10 human cancer cell lines. Moreover, Lee et al (33) reported that F3-2-5 isolated from a culture supernatant of Streptomyces sp. induced apoptosis of HeLa cells.…”
Section: Discussionmentioning
confidence: 99%